2014
DOI: 10.1017/jns.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Mannoheptulose has differential effects on fasting and postprandial energy expenditure and respiratory quotient in adult Beagle dogs fed diets of different macronutrient contents

Abstract: The present study aimed to determine the effects of mannoheptulose (MH) (8 mg/kg) on energy expenditure (EE), respiratory quotient (RQ) and glycaemic response in healthy adult Beagle dogs (n 8; 9·62 (sem 0·31) kg; body condition score 4·5). The study was designed as replicated 4 × 4 Latin squares with a 2 × 2 factorial treatment structure. The dietary treatments were low carbohydrate (CHO) relative to fat diet (LC; 31 % CHO, 28 % fat) with placebo (0 mg/kg) or MH supplement and high CHO relative to fat diet (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 34 publications
3
31
1
Order By: Relevance
“…In Labrador Retrievers fed a dietary dose of 4 mg/kg, decreases in post-prandial energy expenditure and respiratory quotient (RQ) were observed [ 9 ]. Conversely, in Beagles fed an oral cocoa butter based supplement containing 8 mg/kg BW MH with a high carbohydrate relative to fat diet, an increase in post-prandial energy expenditure was noted [ 10 ]. Neither study observed changes in serum glucose or insulin with MH feeding.…”
Section: Introductionmentioning
confidence: 99%
“…In Labrador Retrievers fed a dietary dose of 4 mg/kg, decreases in post-prandial energy expenditure and respiratory quotient (RQ) were observed [ 9 ]. Conversely, in Beagles fed an oral cocoa butter based supplement containing 8 mg/kg BW MH with a high carbohydrate relative to fat diet, an increase in post-prandial energy expenditure was noted [ 10 ]. Neither study observed changes in serum glucose or insulin with MH feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Like McKnight, Flickinger, France, et al. () and McKnight, Root‐McCaig et al. (), the diet used in the present study had high inclusion of dietary sorghum which has been demonstrated to minimize post‐prandial glucose and insulin responses in dogs (Carciofi et al., ), making it difficult to observe notable changes in glucose metabolism associated with MH feeding, especially in healthy adult animals receiving superior veterinary care.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, McKnight, Flickinger, France, et al. () demonstrated that plasma MH concentrations peak within 3 hr of ingestion and return to non‐detectable levels within 24 hr of ingestion of a dietary MH supplement (8 mg/kg BW). These findings demonstrate that ingested MH is absorbed and available to the animal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations